Patterns of multiple risk exposures for low receptive vocabulary growth 4-8 years in the Longitudinal Study of Australian Children - Taylor, Catherine L.; Taylor, C; Zubrick, S; Zubrick, Stephen R.; Christensen, Daniel (My University, 2017)
Risk exposures and predictions of child development outcomes typically estimate the independent effects of individual exposures. As a rule though, children are not exposed piecemeal to individual or single risks but, rather, they are exposed to clusters of risk. Many of these clusters of risks are better thought of as comprising a developmental “circumstance” with a substantial duration, over which period, additional risk exposures also accumulate. In this paper we examined the distribution of 16 single risk exposures for low language ability using latent class analysis across a sample of approximately 4000 children from the Longitudinal Study of Australian Children. The best fitting model identified six distinct classes. 46% of children were in a Developmentally Enabled group, 20% were in a group typified as Working Poor families, 10% of children were in group typified as Overwhelmed group, 9% of children were in a group defined by Child Developmental Delay, 8% of children were in a group defined by Low Human Capital, and 7% of children were in a group defined by Resource Poor non-English Speaking background families. These groups had quantitatively and qualitatively distinct patterns of risk factors, and showed different onward trajectories of receptive vocabulary. Our results demonstrate a range of multiple risk profiles in a population-representative sample of Australian children, and highlight the mix of risk factors faced by children. Children with distinct patterns of risk factors have different onward trajectories of receptive vocabulary development.
PLOS One
Keywords: Children; Education and Training -- Literacy and numeracy; Learning, education and training; Education and Training; Children; Literacy and numeracy; Learning, education and training